A new technique for mounting and testing frame-supported homograft aortic valves. Issue 2 (March 1971) - Donnelly, R. J.; Dexter, F.; Deverall, P. B.; Watson, D. A.
Abstract : The mounting of homograft aortic valves on rigid frames often produces cusp distortion leading to mechanical dysfunction. This dysfunction can be demonstrated by a simple testing apparatus. A technique of valve mounting has been developed which consistently results in a competent valve with exact and correct cusp apposition. It is clear that the effect of different techniques of sterilization and preservation on valve function cannot be adequately assessed unless valves are mechanically correct at the time of insertion.